Bir hal yapısında ekonomik sistem araştırması - Karakuş, Yasin Suat (Fen Bilimleri Enstitüsü, 1997)
Bu çalışmada çerçeve açıklığı belli olan bir alanda çelik malzeme kullanılarak ekonomik sistem aranmıştır. Çözüm yöntemleri ve malzeme özellikleri verildikten sonra ilk olarak çerçeve aralığının 7.50 m' den 10.0 m' ye kadar değiştiği durumlar için farklı aşık aralıklarında en uygun açıklıklar aranmıştır. Seçilen aralıklar için sistem dolu gövdeli yapma kiriş olarak ele alınarak statik ve mukavemet hesaplan yapılmıştır. Bulunan sonuçlar çerçeve aralığı 7.7 m olan, uygulamada yapılmış, bir kafes çerçeve çözümü ile ekonomiklik bakımından karşılaştırılmıştır. Seçilen aralıklar için kalkan cephe, yan cephe, stabilite bağlantısı ve temel hesaplan da ayrıca verilmiştir. Xİİ

The main purpose of this study, is to compare different types of steel structural systems to have an economical result. Firstly, it was given necessary material properties, solution methods and loads. These loads are dead loads, self weight of the system, snow load (2. Region), wind load and earthquake load. Then, it was tried to find the most suitable purlin (frame to frame distances) span length for two different purlin to purlin distances. The purlins, that are continuous, placed on the roof, serve to distribute the roof loads between the frames. First: n=10 opening a=1730mm Second: n=14 opening a=1235 mm a: distance between purlins For this purpose, purlin spans were taken from 7.5 m to 10 m by increasing 0.5 m, for the given frame length 35 m and the structural conditions. For every increasing of purlin spans, it was solved necessary purlin sections and displacements for two different purlin to purlin distances above. At the end of this step, it was chosen 7.50 m span length and 1730 mm purlin to purlin distance. The reasons of this chosen are: 1. If a=1730mm then weight is 8.30 kg/m2 If a=1235 mm then weight is 8.99 kg/m2 for 7.50 m purlin span. 2. For distance between purlins a=1235 mm and purlin span 1 greater than 7.50 m, then it is hard to construct the stability members. 3. For every 50 cm increasing of purlin span lengths, does not effect the type of cross-section much. 4. For a=1235 mm and 1=7.50 m the displacement of the purlin exceeds the limits. Then, for chosen purlin section, necessary stress and stability controls were made. Add of purlins, peak and eavestrough purlins were calculated. Peak and xw eavestrough purlins were chosen same cross-section such as other purlins. Because, if we use smaller cross-sections then it becomes hard to put the roof coatings on the purlins. Finally, chosen system area became (7.50*13)*35.0 m thirty to ninety-seven points five meters. All of the other calculations will be performed for these chosen distances. For chosen distances, given plane frame in figure I. a solved for fixed end and hinged end to the ground for three different loads conditions to find which system is economical and which load condition is inconvenient. These load conditions are: 1. Total dead loads 2. Total dead loads + earhquake loads 3. Total dead loads + wind loads. At the end of solution, plane frame system was chosen hinged to the ground and inconvenient load condition is total dead loads. The reasons for this: 1. Maximum moments, found from static analysis for two different type of frame are close to each other. 2. Moment carrying capacity of the cross-section exceeds at the bottom of the column. 3. Column base can construct more difficulty in the case of fixed end frame. Because it carries also moment loads. Then, for chosen distances and solution method (hinged), system was solved to find a suitable cross-section. For this purpose, given frame in figure I-a, divided into many nodes. These nodes are at the each 100 cm in vertical and 75 cm in horizontal. At the end of solution, an haunched frame system was obtained and first croos-section were obtained. After that, necessary stress and stability controls were made for this cross-section for frame beams and columns. Also, it was calculated beam add detail. Columns at the first frames and roof stability members were dimensioned. Then side frames were analyzed for wind and earthquake loads. Also, it was chosen second cross-section in order to have the frame without a haunch. After this solution, it was chosen first cross-section and all of the calculations were made for this section. The reason of this: Frame system for second cross- section becomes heavier and more expensive than first cross-section. For first cross-section the weight of one frame is nearly 6.49t and for second cross-section it is nearly 7.09 1. xiv At the second step, given truss system in figure Lb that is used system (by EVYAP), was compared with the first system in terms of economy. Used truss system nearly has the same dimensions as the first system. At the end of the calculations two frame systems were compared for weight, workmanship and usage of the structure volume. 1. Comparing for weight: Weight of truss system: nearly 4.3 tons. Weight of the first system: nearly 6.9 tons. It can be easily shown that truss system is more economical for weight. For truss system distance between frames are 7.70 m. This gives more advantage to truss system. 2. Comparing for workmanship: For workmanship we can not say an exact result. Because many factors effects the cost of the workmanship such as types of welding machines, cost of workers and may be time of the construction. 3. Comparing for structure volume: Truss system reduces the structure volume more than first system. The height of truss system is nearly 155 cm, but it is 78 cm for first system. This characteristic sometimes can be important and it makes first system more serviceable for volume usage. Static analysis for the plane frame, roof stability members and side frames was made by SAP90 static analysis program. For these analysis's data and output files were given in additional parts (Add A, B, C, D) In this study, the stress and stability controls of the members have been performed in accordance with the Turkish Standards. For tension members: Fn: Net cross-sectional area ° = y--cr« Turkish Standards allow an upper limit for the slenderness ratio of compression members. XV For compression members: (TS648- Title 3.2.2.1) K=-r*- veya A_=-^ 1. A-^bb(^>^v) N a = w x - < a an ?.-£ >*-# For the members subjected to axial force and bending moment: (TS648- Title3.4) eb + ?= e.»**,* ^my X ^by ban and a j °"eb <="" ?±-="" if="" but="" ©- a \/ V 7\ V 7\ \/ 7K V 7" V PIR \/ /\ \ \ 7\ V V / \ / /\ l~r\. 7\/3 /\ \/ /\ \/ A V 7\ /\_UJ 7" v 7\ V 7\ V : 064 0Si£ OS/1 r UJ < 1 < Şekil T-a - Dolu Gövdeli Çerçeve Sistemi XVIII <|-=h <(^H C/J
The search of an economical system for a steel structure and comparing with a structure used in market place
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Ekonomik sistemler; Çelik malzemeler; Çerçeve; Economic systems; Steel materials; Frame